Le Bras, H. (2016), Anatomie sociale de la France, París, Robert Laffont - Urteaga, Eguzki (Estudios Demográficos y Urbanos, 2017)
Le Bras, H. (2016), Anatomie sociale de la France, París, Robert Laffont